Emerging options for the management of scorpion stings - Chippaux JP (Dove Medical Press, 2012)
Jean-Philippe ChippauxUMR 216 (Institute of Research for Development and University Paris Descartes, Sorbonne Paris Cité), Cotonou, Bénin, FranceAbstract: Scorpion stings are common in many tropical countries. Although most scorpion stings cause only localized pain without life-threatening envenoming, about one third of stings cause systemic envenoming which can result in death. Children are particularly sensitive to scorpion envenoming. The severity of scorpion stings is related to the presence of neurotoxins in the venom that cause a sudden release of neurotransmitters from the autonomic nervous system, predominantly sympathetic. There is also a strong inflammatory response that worsens symptoms, including those of a respiratory nature. Several vital functions may be directly affected, including the cardiovascular, respiratory, and neuromuscular systems. Hypertension is constant at the beginning of systemic envenoming and sometimes has a severe cardiac and respiratory impact. Although controversial, immunotherapy is the only etiological treatment. Administered early, it prevents many complications and improves the outcome. New antivenoms are highly purified immunoglobulin fragments, the efficacy and safety of which are excellent. As a consequence, adverse reactions to antivenoms are now very rare and usually mild, which should limit any reluctance regarding their routine use. Symptomatic treatment is still necessary to support immunotherapy, especially in cases of delayed arrival at hospital. A combination of both approaches should be considered, based on local resources and constraints.Keywords: scorpion, envenoming, treatment, antivenom